2020
DOI: 10.17707/agricultforest.66.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Citrates Nanoparticles on Morphological Traits of Bacterial Cells Pseudomonas Syringae Рv. Atrofaciens

Abstract: Electron microscope investigations have revealed disintegration of the cell wall of Pseudomonas syringae pv. atrofaciens and subsequent killing of bacterial cells after application of 1% solutions of the citrates of Ag-Cu nanoparticles, the complex Co-Cu-Zn-Fe-Mn-Mo-Mg (Avatar-1) and iodine-selenium. In field conditions, it was revealed that pre-sowing treatment of wheat seeds with the aforementioned 1% solutions significantly inhibited the development of basal glume rot in cereals with artificial infection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Nanoparticles of Au, Ag, alumina (Al), Se, titanium dioxide (TiO 2 ), silicon dioxide (SiO 2 ), copper oxide (CuO), zinc oxide (ZnO), calcium oxide (CaO) and magnesium oxide (MgO) have a proven antimicrobial action (Karimi, 2019;Filipović et al, 2021). Antimicrobial activity of Ag-Cu, complex Co-Cu-Zn-Fe-Mn-Mo-Mg, biological substance of I-Se, and each nano chelates of V and Ge, have been shown (Huliaieva et al, 2020). Known that MoO 3 nanoparticles has high antimicrobial activity against gram-negative and gram-positive bacteria, Candida albicans and Aspergillus niger and the ability to remove free radicals (Fakhri & Nejad, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles of Au, Ag, alumina (Al), Se, titanium dioxide (TiO 2 ), silicon dioxide (SiO 2 ), copper oxide (CuO), zinc oxide (ZnO), calcium oxide (CaO) and magnesium oxide (MgO) have a proven antimicrobial action (Karimi, 2019;Filipović et al, 2021). Antimicrobial activity of Ag-Cu, complex Co-Cu-Zn-Fe-Mn-Mo-Mg, biological substance of I-Se, and each nano chelates of V and Ge, have been shown (Huliaieva et al, 2020). Known that MoO 3 nanoparticles has high antimicrobial activity against gram-negative and gram-positive bacteria, Candida albicans and Aspergillus niger and the ability to remove free radicals (Fakhri & Nejad, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it has been found that pre-treatment with a 1% I-Se solution signifi cantly damages P. syringae pv. atrofaciens cells and inhibites the development of basal glume rot on wheat plants aft er an artifi cial infection with this pathogen [19].…”
mentioning
confidence: 99%